2015
DOI: 10.4236/as.2015.63030
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Secondary Bacterial Metabolites in the Control of Citrus Canker

Abstract: This study investigated the protective effects of secondary bacterial metabolites, produced by Pseudomonas sp. (bacterium strain LN), on citrus canker disease caused by Xanthomonas axonopodis pv. citri (Xac 306). The LN bacteria strain was cultured in liquid medium and the supernatant free-cells was treated with methanol (AMF) and ethyl acetate (AEF), respectively, and then the extract was concentrated, filtrated, lyophilized and fractionated by vacuum liquid chromatography (VLC). After VLC, eight fractions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
(18 reference statements)
1
11
1
Order By: Relevance
“…The chemotherapeutic potential of Fluopsin C has been highlighted since its first description, but the significant cytotoxicity against Ehrlich, Hela, and sarcoma 180 cells line, added to acute toxicity in animal models, suggested its unfeasibility to control infections in humans (Itoh et al, 1970; Otsuka et al, 1972). Fluopsin C also increased CC 50 / 24 h when compared to previous studies with semi-purified fractions, where the cytotoxicity was not detected with F3 and F3d fractions (Murate et al, 2015; Kerbauy et al, 2016). Probably, the activity of these fractions against LLCMK2 cell line was low because Fluopsin C was diluted in these fractions.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The chemotherapeutic potential of Fluopsin C has been highlighted since its first description, but the significant cytotoxicity against Ehrlich, Hela, and sarcoma 180 cells line, added to acute toxicity in animal models, suggested its unfeasibility to control infections in humans (Itoh et al, 1970; Otsuka et al, 1972). Fluopsin C also increased CC 50 / 24 h when compared to previous studies with semi-purified fractions, where the cytotoxicity was not detected with F3 and F3d fractions (Murate et al, 2015; Kerbauy et al, 2016). Probably, the activity of these fractions against LLCMK2 cell line was low because Fluopsin C was diluted in these fractions.…”
Section: Discussioncontrasting
confidence: 53%
“…The development of molecules complexed with metals as potential medicinal agents has been rising the last decade (Cardozo et al, 2013; de Oliveira et al, 2016; Kerbauy et al, 2016; Munhoz et al, 2017; Stringer et al, 2017). Previous studies demonstrated that specific fractions obtained from the culture of Pseudomonas aeruginosa LV strain (F3, F3D, and F4A) present very strong antimicrobial activity against many different pathogens (de Oliveira et al, 2011, 2016; Cardozo et al, 2013; Murate et al, 2015; Kerbauy et al, 2016; Munhoz et al, 2017; Simionato et al, 2017). Indeed, our research group demonstrated the strong antibiotic activity of these semi-purified fractions against planktonic cells and biofilm formation of MDR isolates (Kerbauy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed a bacteriolytic effect on X. citri without any sign of phytotoxicity (de . In addition, other secondary metabolites from P. aeruginosa prevented canker formation at low micromolar concentration (Murate et al 2015;Spago et al 2014). However, as P. aeruginosa is an opportunistic human pathogen, the use this bacterium as a biocontrol agent presents risks and, therefore, needs to be strictly regulated.…”
Section: Biological Controlmentioning
confidence: 99%
“…At each stage, the Erlenmeyer flask was shaken with slow rotation. The ethyl acetate fraction was concentrated using a rotatory evaporator and the crude extract was then dissolved in dimethyl sulfoxide (DMSO) at a concentration of 1 mg/ml and stored at 4°C [24].…”
Section: Preparation Of Quorum Quencher Endophytic Bacterial Extractsmentioning
confidence: 99%